Detection and Classification of Multi-Type Cells by Using Confocal Raman Spectroscopy - Wen, Jing; Tang, Tianchen; Kanwal, Saima; Lu, Yongzheng; Tao, Chunxian; Zheng, Lulu; Zhang, Dawei; Gu, Zhengqin (Frontiers in Chemistry, 2021)
Tumor cells circulating in the peripheral blood are the prime cause of cancer metastasis and death, thus the identification and discrimination of these rare cells are crucial in the diagnostic of cancer. As a label-free detection method without invasion, Raman spectroscopy has already been indicated as a promising method for cell identification. This study uses a confocal Raman spectrometer with 532 nm laser excitation to obtain the Raman spectrum of living cells from the kidney, liver, lung, skin, and breast. Multivariate statistical methods are applied to classify the Raman spectra of these cells. The results validate that these cells can be distinguished from each other. Among the models built to predict unknown cell types, the quadratic discriminant analysis model had the highest accuracy. The demonstrated analysis model, based on the Raman spectrum of cells, is propitious and has great potential in the field of biomedical for classifying circulating tumor cells in the future.